Collective scaffolding in virtual collaborative writing: A study during emergency remote teaching in Indonesia - Hanna Sundari; Rina Husnaini Febriyanti (Studies in English Language and Education, 2023)
Along with online education and emergency remote teaching trends during the COVID-19 pandemic, collective scaffolding within virtual collaboration in an academic writing course is still under investigation. To fill the gap, this present study explored to what extent the collective scaffolding provided in virtual collaborative writing helped learners complete writing tasks and examined EFL university students’ responses to this learning activity. Guided by a qualitative case study design framework, 43 EFL university students, who attended an academic writing course, voluntarily participated in the study. The data were collected through multiple sources during the virtual writing course, such as students’ work artifacts (photographs and descriptions), an online questionnaire, and teacher’s written reflective journals of Zoom class video recordings as the research instruments. A thematic analysis with a category system was applied to answer the formulated research questions. The findings reveal that collective scaffolding occurred during collaborative writing in the text co-construction during the writing process. Further, collaborative writing allowed L2 improvements, mutual support, and contribution. Additionally, the activity of assisting and monitoring by the teacher was still significant during group deliberation and text development. Although technology-assisted collaborative writing sounds possible and affordable, a few students felt disappointed as they experienced some technological constraints and unexpected group dynamics. Some groups successfully achieved the tasks and social dimensions easily; while others needed a longer time to reach the group development and text productivity.